Identification of Immunosuppressive Medication Nonadherence Factors Through a Combined Theory Model in Renal Transplant Recipients - Zhang, Pengpeng; Zhu, Xiao; Yan, Jin; Liu, Jia (Frontiers in Pharmacology, 2021)
Background: Immunosuppressive medication (IM) nonadherence is associated with poor transplant outcomes. Therefore, it is of great importance to identify predictive factors with IM nonadherence. We aimed to improve the predicted capacity of the Theory of Planned Behavior (TPB) by adding Health Belief Model’s variables (HBM) in renal transplant patients (RTPs). Methods: This cross-sectional study distributed questionnaires to patients who had undergone renal transplant and follow-up regularly in the transplant center of Third Xiangya Hospital in China. The self-developed questionnaire collected data in three aspects: General Data Questionnaire, TPB and HBM specific questionnaire, Basel Assessment of Adherence to Immunosuppressive Medications scale. Results: A total of 1357 of 1480 patients completed the survey, with a participation rate of 91.69% and IM nonadherence rate of 33.53%. The marital status, household income, preoperative drinking history, the time after transplantation and religion showed independent predictive factors with IM nonadherence (p<0.05). Strikingly, adding HBM variables to TPB theory model significantly increased its prediction ability to IM nonadherence (52%). And HBM manifested the highest coefficient of effect (-0.620). Particularly, perceived barriers and perceived seriousness, the variables of HBM model, played a vital influence on medication nonadherence (-0.284 and 0.256). Conclusion: Our study here reveals the first investigation of the combined effects of TPB and HBM model on IM nonadherence in Chinese RTPs, which could significantly improve the predictive ability of any single models. Meanwhile, future interventions should be conducted to both increase perceived seriousness and reduce perceived barriers for taking IM, which will effectively decrease IM nonadherence rates and improve transplant outcomes.